Benchmarking practice for ports terminal operations: A comparative study between theoretical and practical approaches - Faruquee, Murtaza (2015)
In global logistics and transportation network shipping ports play a very important role. Significance of shipping port has increased tremendously for development of global economy. Approximately 500 million tonnes cargo was handled by sea ports in 1950, which become 7 billion tonnes in 2005. In this era of globalization, shipping ports’ terminal operations efficiency becomes very relevant for global logistics. Answering questions about efficiency is very complicated, first of all indicators of one performance criteria is not enough to get overall conclusion, but few indicators of different criteria would be miss leading too. It is quite a serious question to answer that, what actually need to be measured to compare port terminal operations among different ports and how those indicators get perceived by real industry practitioner. Benchmarking has been proven as an effective method to understand performance and enhance knowledge base of organization. Through the benchmarking process and also final findings from benchmarking, both create significant impact on the operational strategy. This is also very useful for terminal operations too. To understand the impact of benchmarking on terminal operations, analysis needs to conduct from two different angles. One is academic researchers’ point of view on benchmarking and then terminal operators’ understanding about use of benchmarking in their operations. This research includes an intensive literature review to indicate academic researchers’ approaches on terminal operations benchmarking and overall understanding of benchmarking process. After that, this project conducts a small survey followed by in-depth interviews with terminal operators to develop understanding on their way of using benchmarking for performance measurement. Based on all these information and with a help of service blueprint model a clear flow of key activates of terminal has been developed. This model provides insight on what are the key success and failure risk points for terminal operations. This also provides indication regarding which indicators could be monitored to provide efficient service. Moreover, a framework has developed to build a comparative analysis between academic researchers’ approaches and terminal operators’ approaches on benchmarking application. Through this comparative study, some key differences in approaches and primary reason behind these differences become clearer. Due to their strong motivation for developing new theories, academics mostly use very strong and complex theoretical models. Except very few of those, it is very hard to apply these findings directly in real terminal operations. But those have significant academic value and indirect impact on decision making for terminal operators. On the other hand, terminal operators use benchmarking to make sure their operations are improving. Also they have concern about simplicity of the process to ensure that every stakeholder can understand the findings from benchmarking. Certainly there is no way to make a judgment call regarding whose approach is better and trying to do that, is not even necessary. Purpose of this study is providing clear understanding of different approaches. However, these findings will be very helpful for further researches on developing standard benchmarking models for terminal operations.